APLIKASI UNTUK MENYEMBUNYIKAN FILE PADA HANDPHONE MENGGUNAKAN JAVAME - Hajad Adhy Putra; Novrido Charibaldi (Telematika, 2011)
Mobile is now not only as a means to communicate, recently mobile technology / mobile phone, the more feture like java platform provided therein. The latest mobile phones are now equipped with a MMC (MultiMediaCard), which are mostly used to store data in the form of text, image (the images), sound, video clips and scripts. This application is expected to hide the confidentiality of critical data and personal data on a mobile phone. The method used in the design and manufacture of this software is a method Grapple (Guidlines for Rappid Application Engineering), NetBeans IDE 6.0 is used as a tool to help programming. System modeling language used is the Unified Modeling Language (UML). The programming language used was JavaME